2023
DOI: 10.1111/his.14865
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary lymphoid structures in breast ductal carcinoma in situ correlate with adverse pathological parameters

Abstract: Aims: To investigate tertiary lymphoid structures (TLSs) in ductal carcinoma in situ (DCIS) of the breast and their correlation with pathological features, immune cell markers and clinical outcomes. Methods and results: Morphological identification of TLSs in 198 DCIS cases incorporated B and T cell zones with high endothelial venules. TLS positivity was defined as ≥ 1 TLSs in lesional areas, while TLS area percentage was divided into two categories: low (TLSs < 5%) and high (TLSs ≥ 5%). Previously reported bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…This suggests that the patch-or tile-based approaches for image analysis used in many studies are inappropriate, which may lead to misestimation of the presence of TLSs. Zeng et al (21) reported that the percentage of TLS-positive breast ductal carcinomas was 24.7%, which is signi cantly different from the 60.3% reported in a Korean study (22).…”
Section: Discussionmentioning
confidence: 63%
“…This suggests that the patch-or tile-based approaches for image analysis used in many studies are inappropriate, which may lead to misestimation of the presence of TLSs. Zeng et al (21) reported that the percentage of TLS-positive breast ductal carcinomas was 24.7%, which is signi cantly different from the 60.3% reported in a Korean study (22).…”
Section: Discussionmentioning
confidence: 63%
“…In urothelial cancer, some studies included noninvasive urothelial carcinoma, although there is no description of the extent to which TLSs are contained in these noninvasive cancers and there is also no description of the correlation of intraepithelial carcinoma and TLSs. 24,25 One report describes that TLSs are also present in ductal carcinoma in situ of breast, 26 but further studies may be needed to better define the relationship between TLSs and carcinoma in situ.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between the immune component and other TME components such as stromal blood vessels or tumor stromal myofibroblasts are still less elucidated [ 31 , 32 , 33 , 34 ]. The TLSs impact on tumor progression, lymphovascular invasion, perineural invasion, and recurrence remain the most questionable and neglected chapters in the field [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%